Handbook of algal technologies and phytochemicals - Ravishankar, Gokare A.; Ranga Rao, Ambati (Milton : CRC Press LLC, 2019)
This two-volume set explores the aspects of diversity of micro and macro algal forms, their traditional uses; their constituents which are of value for food, feed, specialty chemicals, bioactive compounds for several novel applications and bioenergy molecules. The industrial production systems, downstream processing, utilization of the biomass and the metabolites of importance for various applications are addressed. Innovations in production technologies, coupled with the biological activities of their novel metabolites and molecules, offer tremendous scope for the exploitation of these micro and macro algal forms through industrial production processes in a sustainable manner. These two volumes offer a treasure house of information to the students and researchers of plant sciences, biological sciences, agricultural sciences, foodsand nutrition sciences, health sciences and environmental sciences. Their practical value will benefit professionalsincluding agricultureand food experts, biotechnologists, ecologists, environmentalists, and biomass specialists. This set will also aidindustries dealing with foods, nutraceuticals, pharmaceuticals, cosmecuticals health care products, and bioenergy.
Key Features The most comprehensive resource available on the biodiversity of algal species, their industrial production processes and their use for human consumption in food, health and varied applications. Emphasis on basic and applied research, addressing aspects of scale-up for commercial exploitation for the development of novel phytochemicals (phytochemicals from algae). Addresses the underexplored and underutilized potential of chemicals from marine sources for health benefits. Each chapter, written by expert contributors from around the world, includes a Dictionary of Terms, Key Facts, Summary Points, Figures and Tables, as well as up-to-date references. The second book in this two-volume set explores phycoremedation applications, and the sustainable use of algae for biofuels and other products of economic value. It also looks at aspects such as macro- and micro algal impact on marine ecosystem and remote sensing of algal blooms. The commercial value of chemicals of value to food and health is about $6 billion annually, of which 30 percent relates to micro and macro algal metabolites and products for health food applications. As a whole, the two volumes explore the aspects of diversity of micro and macro algal forms, their traditional uses; their constituents which are of value for food, feed, specialty chemicals, bioactive compounds for novel applications, and bioenergy molecules. Bio-business and the market share of algae-based products are also dealt with, providing global perspectives.
Chapter 23: Functional Omics and Big Data Analysis in Microalgae: The Repertoire of Molecular Tools in Algal Technologies -- Chapter 24: Bioactive Metabolites: Genetic Regulation and Potential Market Implications -- Chapter 25: Leveraging Genome Sequencing Strategies for Basic and Applied Algal Research, Exemplified by Case Studies -- Index -- Volume 02 -- Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Preface -- Acknowledgments -- Editors -- Contributors -- SECTION I: Phycoremediation Applications
Chapter 1: Wastewater Phycoremediation by Microalgae for Sustainable Bioproduct Production
OCLC-licensed vendor bibliographic record.
Keywords: Algae products; Algae -- Biotechnology; SCIENCE -- Life Sciences -- General; SCIENCE -- Life Sciences -- Biology -- Marine Biology; MEDICAL -- Biotechnology; SCIENCE / Life Sciences / General; SCIENCE / Life Sciences / Biology / Marine Biology; MEDICAL / Biotechnology